Implementasi Kebijakan Penanaman Modal Pada Kantor Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Provinsi Sulawesi Tengah - WAHYU, EKA WAHYU PRADIUTAMA; Rivai, Abdul; Sri Astuti, Agusta (JPS: Journal of Publicness Studies, 2024)
This study aims to determine the implementation of investment policies at the Central Sulawesi Province One-Stop Investment and Integrated Services Service. The research method used is descriptive qualitative, which is to provide an overview of the phenomenon or focus of the problem under study that occurs at the research location according to existing facts. The data collection techniques used are observation, in-depth informant interviews and documentation to collect the required data in the form of primary and secondary data. Meanwhile, there were 3 informants in this study, namely from the Central Sulawesi Province Department of Investment and One Stop Integrated Services (DPMPTSP). The theory used in this study is George C. Edward III theory where there are four indicators used in the stages of implementing investment policies at the Central Sulawesi Province Investment and One-Stop Integrated Services Service. The four indicators are communication, resources, disposition and bureaucratic structure. Based on the results of the study, it shows that the implementation of investment policy at the Central Sulawesi Province One-Stop Investment and Integrated Services Service has gone well on several indicators, namely communication, disposition and bureaucratic structure. Meanwhile, the resource indicators have not gone well. This can be seen from the lack of competent staff at the Central Sulawesi Province One Stop Investment and Integrated Services Service (DPMPTSP), as well as the inadequate facilities and infrastructure at the Provincial Investment and One Stop Integrated Services Office (DPMPTSP) Central Sulawesi. All forms of these problems need repair and overhaul so that they run well in the future. Keyword: Policy Implementation, Investment, Communication, Resources, Disposition, Bureaucratic Structure.